Economic openness and welfare state attitudes: A multilevel study across 67 countries. (29th April 2013) - Koster, Ferry
<x xml:space="preserve">Abstract</x> This article extends previous studies investigating economic globalisation and the welfare state by examining individual attitudes, ranging from a preference for individual responsibility (economic individualism) to public demand for government intervention (social equality), across a large number of countries. It formulates different hypotheses about the direct and moderating effects of economic openness on these attitudes. The multilevel analysis, investigating data from 99, 663 citizens of 67 countries, leads to the following two conclusions. First, economic openness is associated with a stronger preference for economic individualism and less demand for government intervention. Second, groups benefiting from globalisation and right‐wing voters have a stronger preference for economic individualism if the economic openness of their country is higher. Key Practitioner Message: ● The results show that some vulnerable groups demand more social protection in economically more open countries.